2014
DOI: 10.1074/jbc.m113.508457
|View full text |Cite
|
Sign up to set email alerts
|

Remodeling of Marrow Hematopoietic Stem and Progenitor Cells by Non-self ST6Gal-1 Sialyltransferase

Abstract: Background: The circulatory ST6Gal-1 level is inversely related to hematopoietic activity, but the biochemical function of systemic ST6Gal-1 is unknown. Results: Hematopoietic progenitors do not express self-ST6Gal-1 but are acted upon by remotely produced enzyme. Conclusion: Distally produced rather than endogenous ST6Gal-1 is the principal modifier of the early hematopoietic progenitor cell surface. Significance: Extrinsic ST6Gal-1 may be a potent systemic regulator of hematopoiesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…In a separate study, we showed that the surface ␣2,6-sialyl structures of hematopoietic progenitor cells were generated exclusively by extrinsic ST6Gal-1 rather than the endogenously expressed enzyme, and the action of the extrinsic sialyltransferase resulted in hematopoietic arrest (15). Here, we demonstrate that activated platelets can functionally support extrinsic ST6Gal-1 sialylation of hematopoietic progenitor cells.…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations
“…In a separate study, we showed that the surface ␣2,6-sialyl structures of hematopoietic progenitor cells were generated exclusively by extrinsic ST6Gal-1 rather than the endogenously expressed enzyme, and the action of the extrinsic sialyltransferase resulted in hematopoietic arrest (15). Here, we demonstrate that activated platelets can functionally support extrinsic ST6Gal-1 sialylation of hematopoietic progenitor cells.…”
Section: Resultsmentioning
confidence: 78%
“…Glycans occupy the critical interface between each cell and its outside environment. Extrinsic glyco- syltransferases, such as the circulatory ST6Gal-1, can alter cell behavior by remodeling the glycan interface (15). Because circulatory ST6Gal-1 is freely available, platelets may serve as a pivotal moderator of glycosylation by controlling the release of the necessary substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, STs were thought to localize exclusively within the intracellular secretory apparatus (50). A growing number of studies report ST activity in serum or on surfaces of the cells of immune system, including polymorphonuclear leukocyte, monocyte-derived dendritic cells, lymphocytes, and T cells (48,49,(51)(52)(53)80). Presence of ST on the cell surface or in serum allows rapid restoration or remodeling of the sialylation status of cells without de novo synthesis of cell surface glycoconjugates (48,49,81).…”
Section: Although Degradation Of Prpmentioning
confidence: 99%